A case study of ozone production, nitrogen oxides, and the radical budget in Mexico City - E. C. Wood; S. C. Herndon; T. B. Onasch; J. H. Kroll; M. R. Canagaratna; C. E. Kolb; D. R. Worsnop; J. A. Neuman; R. Seila; M. Zavala; W. B. Knighton (Atmospheric Chemistry and Physics, 2009)
Observations at a mountain-top site within the Mexico City basin are used to characterize ozone production and destruction, nitrogen oxide speciation and chemistry, and the radical budget, with an emphasis on a stagnant air mass observed on one afternoon. The observations compare well with the results of recent photochemical models. An ozone production rate of ~50 ppbv/h was observed in a stagnant air mass during the afternoon of 12 March 2006, which is among the highest observed anywhere in the world. Approximately half of the ozone destruction was due to the oxidation of NO2. During this time period ozone production was VOC-limited, deduced by a comparison of the radical production rates and the formation rate of NOx oxidation products (NOz). For [NOx]/[NOy] values between 0.2 and 0.8, gas-phase HNO3 typically accounted for less than 10% of NOz and accumulation-mode particulate nitrate (NO3(PM1)−) accounted for 20%–70% of NOz, consistent with high ambient NH3 concentrations. The fraction of NOz accounted for by the sum of HNO3(g) and NO3(PM1)− decreased with photochemical processing. This decrease is apparent even when dry deposition of HNO3 is accounted for, and indicates that HNO3 formation decreased relative to other NOx "sink" processes during the first 12 h of photochemistry and/or a significant fraction of the nitrate was associated with the coarse aerosol size mode. The ozone production efficiency of NOx on 11 and 12 March 2006 was approximately 7 on a time scale of one day. A new metric for ozone production efficiency that relates the dilution-adjusted ozone mixing ratio to cumulative OH exposure is proposed.